(untitled) (Minerva. Revista de Filología Clásica, 2019)
Reseña de M. Foley (ed.), A Companion to Ancient Epic. Blackwell Companions to the Ancient World, Oxford, Blackwell, 2005. XXV+664 págs., 11 ilustraciones, 1 mapa. ISBN-13: 978-1-4051-0524-8